Sedulur Sikep’s Sociocultural Adaptation to Social Changes in Ploso Kedhiren Village, Randublatung District - Rahmatillah, Hamida Zama; Demartoto, Argyo; Kartono, Drajat Tri (Yayasan Ilomata, 2025)
Sedulur Sikep refers to the followers of Samin Surosentiko’s teachings that continue to exist to this day by consistently upholding the values and teachings of Samin. This research aims to explore the sociocultural adaptation strategies employed by Sedulur Sikep. The research was conducted from January to March 2025. This study utilizes a qualitative method and phenomenological approach. The data collection techniques include three methods, which are observation, interviews, and documentation. The sampling technique applied in this study is purposive sampling. The obtained data were analyzed by reducing, displaying data, drawing conclusions, and verifying them. The results indicate that Sedulur Sikep adhere to the Samin’s teachings, which fundamentally focus on principles of human life values that serve as a guide for attitudes and behavior, especially for the Sedulur Sikep to remain virtuous and honest. The challenges faced by the Sedulur Sikep are inseparable from the context of social pressures and domination they experienced, particularly during politically sensitive periods, such as the post-G30S/PKI 1965 era. Government policies related to KTP (Resident Identity Card), marriage registration at the KUA (Office of Religious Affairs), and compulsory formal education have influenced the lives of Sedulur Sikep. Findings show that the Sedulur Sikep have maintained the core values of Samin’s teachings while remaining open and willing to adapt to social changes. Future research should focus on the younger generation of Sedulur Sikep to explore their sociocultural adaptation